Essays on Kant's anthropology/ edited by Brian Jacobs and Patrick Kain - "Jacobs,Brian(ed.)" (Cambridge, 2007)
Kant's lectures on anthropology capture him at the height of his intellectual power. They are immensely important for advancing our understanding of Kant's conception of anthropology, its development, and the notoriously difficult relationship between it and the critical philosophy. This 2003 collection of essays by some of the leading commentators on Kant offers a systematic account of the philosophical importance of this material that should nevertheless prove of interest to historians of ideas and political theorists. There are two broad approaches adopted: a number of the essays consider the systematic relations of the anthropology to critical philosophy, especially speculative knowledge and ethics. Other essays focus on the anthropology as a major source for the clarification of both the content and development of Kant's work. The volume also serves as an interpretative complement to the translation of the lectures in the Cambridge Edition of the Works of Immanuel Kant.
Keywords: "Kant, Immanuel"